Performance Assessment of an Interconnected Photovoltaic-Thermal System and Solar Thermal Collector: Parametric Study and Optimization - Karami, Maryam; Heidarnejad, Parisa (WILEY, 2025)
In the present study, an interconnected photovoltaic-thermal system and solar thermal collector with half-tubes are presented as a new generation of solar systems to produce maximum thermal and electrical power. Performance comparison of the photovoltaic module, photovoltaic-thermal system, solar thermal collector, and proposed system shows that the maximum power of 1336.27 W is generated by the proposed system. Also, the outlet fluid temperature increases by 28.03% and 20.88% compared to the photovoltaic-thermal systems and solar thermal collectors, respectively, which indicates higher quality of the generated thermal power. To improve the system performance, fins with different heights are used inside the half-tubes. The results indicated that the overall generated power increases using the fin by up to 2.93%. A parametric analysis using response surface method showed that among four parameters including flow rate, incident solar radiation, wind speed, and ambient temperature, the solar radiation and ambient temperature have the most and least impact on the system output, respectively. Also, using the response surface method, two models are provided to predict the electrical and thermal power generation of the system. Single-objective and multi-objective optimization of the system is also investigated using these models.
Keywords: optimization; photovoltaic-thermal system; response surface method; solar thermal collector; MICROCHANNEL HEAT SINK; ENERGY; NANOFLUIDS; EFFICIENCY; EXERGY; DESIGN; MODEL; Energy & Fuels